2021
DOI: 10.3389/fimmu.2021.642715
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α-Induced Protein 8-Like 2 Negatively Regulates Innate Immunity Against RNA Virus by Targeting RIG-I in Macrophages

Abstract: A systematic and flexible immunoregulatory network is required to ensure the proper outcome of antiviral immune signaling and maintain homeostasis during viral infection. Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2), a novel immunoregulatory protein, has been extensively studied in inflammatory response, apoptosis, and cancer. However, the function of TIPE2 in antiviral innate immunity is poorly clarified. In this study, we reported that the expression of TIPE2 declined at the early period and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…PPP1R15A is usually a target of ATF4 in endoplasmic reticulum stress [ 41 ]. TNF (tumor necrosis factor) encodes proinflammatory cytokines for the TNF family, which is primarily secreted by macrophages [ 42 , 43 ]. TNF is capable of regulating lipid metabolism, cell growth, protein binding, and cytokine activity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPP1R15A is usually a target of ATF4 in endoplasmic reticulum stress [ 41 ]. TNF (tumor necrosis factor) encodes proinflammatory cytokines for the TNF family, which is primarily secreted by macrophages [ 42 , 43 ]. TNF is capable of regulating lipid metabolism, cell growth, protein binding, and cytokine activity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α-induced protein 8-like 2 (TNFAIP8L2, TIPE2) is a newly discovered negative immunoregulatory domain that plays a vital role in regulating inflammatory and cellular immune responses, and is an essential negative regulator of both innate and adaptive immunity by maintaining immune homeostasis [267,268]. TIPE2 appeared to be a critical immunoregulatory molecule involved in the immunosuppressive function of CD4(+)CD25(+) T reg cells [269].…”
Section: Tnf-α-induced Protein 8-like 2 (Tnfaip8l2 Tipe2)mentioning
confidence: 99%
“…Tumor necrosis factor- α -induced protein 8-like 2 (TIPE2), a novel immunoregulatory protein, has been reported to play an important role in regulating the function of macrophages [ 8 , 9 ]. Studies have also confirmed the role of TIPE2 in cancer and cell apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%